2006
DOI: 10.1210/en.2005-1588
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Müllerian Hormone Levels Reflect the Size of the Primordial Follicle Pool in Mice

Abstract: Reproductive aging is the decline of female fertility with age. It is caused by the decrease in the number of growing follicles, resulting from primordial follicle pool depletion. Recently, we have shown that anti-Müllerian hormone (AMH) is produced by growing follicles, and studies in women indicate that serum AMH levels decrease with age and correlate with antral follicle count. However, whether serum AMH levels correlate directly with the size of the primordial follicle pool cannot be determined in women. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
227
3
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(254 citation statements)
references
References 37 publications
13
227
3
11
Order By: Relevance
“…Other researchers have used the fractionator/optical disector technique to estimate the human numbers of primordial follicles (oocyte pools) and determined that the age-adjusted correlation between serum AMH and the oocyte pool is 0.48, which supports the view that AMH reflects the size of the oocyte pool [14]. It has been reported that in 4-to 18-month-old C57BL/6j mice, the serum AMH levels decline with increasing age and directly correlate with declining numbers of growing and primordial follicles [32]. However, in Kevenaar's study, no difference between the AMH levels of 4-and 8-month-old mice was observed.…”
Section: Disscussionsupporting
confidence: 52%
“…Other researchers have used the fractionator/optical disector technique to estimate the human numbers of primordial follicles (oocyte pools) and determined that the age-adjusted correlation between serum AMH and the oocyte pool is 0.48, which supports the view that AMH reflects the size of the oocyte pool [14]. It has been reported that in 4-to 18-month-old C57BL/6j mice, the serum AMH levels decline with increasing age and directly correlate with declining numbers of growing and primordial follicles [32]. However, in Kevenaar's study, no difference between the AMH levels of 4-and 8-month-old mice was observed.…”
Section: Disscussionsupporting
confidence: 52%
“…In mice, the higher production of AMH by small antral follicles reflected the remaining follicle pool (Kevenaar et al 2006). Women of !25 years of age had higher serum AMH concentrations than those aged 35 years and above (Piltonen et al 2005), and when women were followed longitudinally for a period of between 1 and 7 years, there was a decrease in serum AMH levels, with levels becoming undetectable when menopause was reached (Piltonen et al 2005).…”
Section: A Reliable Marker Of Ovarian Function?mentioning
confidence: 97%
“…Thus, AMH seems to downregulate two important steps of follicular development: follicle recruitment and cyclic selection for dominance [9,10]. Mouse studies have shown that AMH serum levels reflect the size of the primordial follicle pool and its reduction with aging [13,27]. In addition, human studies have shown that AMH directly correlates with the number of antral follicles assessed by ultrasound [5] and FSH, inhibin-B and estradiol [11].…”
Section: Introductionmentioning
confidence: 99%